A new bromeligenous species of the Scinax perpusillus group from the hills of the State of Rio de Janeiro, Brazil (Anura, Hylidae) - Da Silva, Helio Ricardo; Alves-Silva, Ricardo (Zootaxa, 2011)
A new species, Scinax insperatus sp. nov., of the S. perpusillus group is described based on specimens collected in the Municipality of Miguel Pereira, State of Rio de Janeiro, Brazil (22 º 13’ 14.6” S and 43 º 26’ 02.1” W). The new species is easily distinguishable from all other species of the S. perpusillus group, except Scinax belloni Faivovich, Gasparini, & Haddad, 2010, by lacking yellow markings in the inguinal region and hidden surfaces of limbs. From Scinax belloni, the new species differs by having dark, metallic-beige colored tubercles on the dorsal surfaces; S. belloni lacks any markings on dorsum, hind limbs, and hidden surfaces, and by lacking inguinal glands. In addition, the tadpoles of the new species are unique among those known for the group in having fins with yellow colored spots in later stages of development.